2021
DOI: 10.1177/21501327211003688
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing FDA’s Reach to Minorities and Under-Represented Groups through Training: Developing Culturally Competent Health Education Materials

Abstract: Health communications may not reach intended populations due to cultural and language barriers. These barriers may prohibit consumers from understanding information needed to make informed health decisions. It is important to ensure everyone—especially racial and ethnic minorities and under-served and under-represented populations—has access to information on medical products. One strategy to address this issue is to develop trainings and resources to better understand how cultural competency affects the abili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…While there is no research, to our knowledge, describing specific concerns related to return to work or education for Aboriginal and Torres Strait Islander AYAs with cancer, financial distress is a common area of unmet need for Aboriginal and Torres Strait Islander adults with cancer in Queensland [ 83 ]. Considering the employment and educational disparities that are known within this population broadly [ 84 , 85 ], it stands to reason that Aboriginal and Torres Strait Islander AYAs with cancer may be in particular need of information to support their educational and employment endeavors. However, resources were generally not inclusive of Aboriginal and Torres Strait Islander peoples.…”
Section: Discussionmentioning
confidence: 99%
“…While there is no research, to our knowledge, describing specific concerns related to return to work or education for Aboriginal and Torres Strait Islander AYAs with cancer, financial distress is a common area of unmet need for Aboriginal and Torres Strait Islander adults with cancer in Queensland [ 83 ]. Considering the employment and educational disparities that are known within this population broadly [ 84 , 85 ], it stands to reason that Aboriginal and Torres Strait Islander AYAs with cancer may be in particular need of information to support their educational and employment endeavors. However, resources were generally not inclusive of Aboriginal and Torres Strait Islander peoples.…”
Section: Discussionmentioning
confidence: 99%
“…The complexity of communities across the US and multifactorial nature of underlying healthcare disparities means there is not a singular solution for improving reporting. Approaches could include tailored educational materials with culturally appropriate messaging delivered through channels that match the preferences of each targeted population [ 60 ]. For some communities with lower reporting rates, such as those we observed with low English literacy, the translation of materials into native languages may be impactful.…”
Section: Discussionmentioning
confidence: 99%
“…For example, work using mediation analysis 5 found that boys in families receiving a housing voucher in the Moving to Opportunities intervention showed an elevated risk of mood and externalizing disorders. Similarly, other research points to how primary prevention interventions can aggravate disparities and social inequities, particularly when they lack cultural humility in their approaches for minoritized populations 6 . Having the perspective of those involved in the program can be critical to optimize the impacts of the prevention interventions and minimize their unintended consequences.…”
mentioning
confidence: 99%